2022
DOI: 10.1002/sce.21705
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' ability to diagnose and deal with alternative student conceptions of evolution

Abstract: Students possess alternative conceptions of many science topics, and these conceptions can act as obstacles for learning scientific concepts. In the field of biology education, students' alternative conceptions of evolution have been widely investigated. However, there is little research on how teachers diagnose and deal with these alternative conceptions, although these abilities are a crucial part of teachers' pedagogical content knowledge. Additionally, little is known about how these abilities are connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…“Evolution is the most profound and powerful idea to have been conceived in the last two centuries” (Diamond, 2001 , p. vii). However, evolution education faces numerous challenges, such as instructors’ lack of sufficient knowledge of evolution (Siani et al, 2022 ), instructors’ poor pedagogical content knowledge to diagnose and deal with student misconceptions of biological evolution (Hartelt et al, 2022 ), student opposition to learning evolution (Siani et al, 2022 ), and the absence of research on misconceptions about evolution in countries, such as Chile, Colombia, Brazil, and Greece. Deniz and Borgerding ( 2018b ) stress that the documentation of evolution education issues around the globe is a necessary step to overcome the multiple challenges of preparing citizens to think critically about the theory of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…“Evolution is the most profound and powerful idea to have been conceived in the last two centuries” (Diamond, 2001 , p. vii). However, evolution education faces numerous challenges, such as instructors’ lack of sufficient knowledge of evolution (Siani et al, 2022 ), instructors’ poor pedagogical content knowledge to diagnose and deal with student misconceptions of biological evolution (Hartelt et al, 2022 ), student opposition to learning evolution (Siani et al, 2022 ), and the absence of research on misconceptions about evolution in countries, such as Chile, Colombia, Brazil, and Greece. Deniz and Borgerding ( 2018b ) stress that the documentation of evolution education issues around the globe is a necessary step to overcome the multiple challenges of preparing citizens to think critically about the theory of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…While this may be according to their intuitive understanding rather than echoing the teacher, the design‐based explanations appeared to be adopted as a pedagogical shorthand. Although the participating teacher's lack of science training may have been an influencing factor (Hartelt et al, 2022), previous research has underscored both the frequent use of pedagogical shorthand in different kinds of material (Gregory, 2009; Moore et al, 2002) and ambivalent stances of biology teachers that involves design‐based and anthropomorphic perspectives (Gresch, 2020; Nehm et al, 2009; Nehm & Schonfeld, 2007). However, supported by disciplinary examples represented by visual support images and whiteboard drawings, the participating teacher adopted a more disciplinary orientation in explanations of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that teachers often have a limited understanding of evolution (Buchan, 2019;Kuschmierz et al, 2020). While findings from Hartelt et al (2022) showed a correlation between teachers' content knowledge and their ability to deal with alternative conceptions, other studies have shown that even teachers with a strong disciplinary background in biology may express intuitive conceptions relating to evolution; for example, that traits arise according to needs or the use or disuse of functions (Nehm et al, 2009;Nehm & Schonfeld, 2007).…”
Section: Understanding Evolution In Biology Teachingmentioning
confidence: 99%
“…In recent years, the usage of the I‐SEA has increased (e.g., Barnes et al, 2019, 2020a, 2020b, 2021a, 2021b, 2022b; Ferguson & Jensen, 2021; Fiedler et al, 2019; Hartelt et al, 2022; Rachmatullah et al, 2018; Romine et al, 2018; Sbeglia & Nehm, 2019, 2020; Wingert et al, 2022), and several new insights into the structure of the scales were presented. For example, Sbeglia and Nehm (2019) found that the scales for microevolution and macroevolution are very stable within a university student sample, while the human evolution scale may be split into two sub‐dimensions (i.e., human microevolution and human macroevolution).…”
Section: Measuring Evolution Acceptancementioning
confidence: 99%